Come away from the water, Shirley - Burningham, John. (London : Random House Children's Books, 2000)
Shirley's adventures at the beach are interspersed with familiar parental warnings.
"First published in Great Britain by Jonathan Cape, 1977"--T.p. verso.
Keywords: Pirates -- Fiction; Seashore -- Fiction; Fantasy